Breastfeeding During Military Service: Different Countries, Different Possibilities - Holmquist, Ivana; Pohnan, Radek; Stritecka, Hana; Spevakova, Barbora; Vasek, Tomas; Bostikova, Vanda (Military medicine, 2021)
INTRODUCTION: Breastfeeding is a human biological norm that is widely acknowledged as the ideal form of nutrition for all infants. Human milk saves lives, improves long-term health for the both mother and infant, and significantly reduces health care-related costs. The American Academy of Pediatrics recommends exclusive breastfeeding for at least 6 months and thereafter to continue with breastfeeding, in addition to complimentary foods for at least 1 year or longer. The World Health Organization extends this recommendation to at least 2 years or beyond this age. MATERIALS AND METHODS: Multiple complex policies and directives would not be necessary if a federal law would entitle all new mothers to an adequate length of paid maternity leave and would protect parents during the time they personally care for their infants. Although a nationally mandated maternity leave is not available, the DoD should create a coherent global policy applicable to all active duty personnel across all branches of the U.S. Military. A global policy would govern positive change across all military branches and create consistent work conditions conducive for mothers to achieve their personal breastfeeding goals. In addition, a global policy would improve the military employees' health as well as maintain retention of military personnel. RESULTS: A comparison of the U.S. Armed Forces to the Czech Armed Forces shows that the individual breastfeeding policies and directives of the U.S. Military branches are certainly steps in the right direction to support breastfeeding military members. CONCLUSION: The well-documented evidence of long-term breastfeeding health benefits in addition to the economic benefits justifies such global military policy and would be a foundation to a national maternity leave policy, given that the USA is the only developed country without nationally mandated statutory entitlement to paid maternity leave.
Keywords: kojení; Salaries and Fringe Benefits; Infant; Humans; Pregnancy; kojenec; ozbrojené síly; dítě; mzdy a přídavky; Child; Female; lidé; Military Personnel; ženské pohlaví; World Health Organization; těhotenství; Breast Feeding; matky; Mothers; Světová zdravotnická organizace